2017
DOI: 10.1093/alcalc/agx066
|View full text |Cite
|
Sign up to set email alerts
|

No Impact of Calorie or Unit Information on Ad Libitum Alcohol Consumption

Abstract: AimsTo investigate the impact of unit and calorie information on drinking behaviour in an ad libitum taste test paradigm.MethodsIn this experimental human laboratory study, participants were randomized to one of four conditions, balanced by gender, using a 2 (unit information: present vs. absent) × 2 (calorie information: present vs. absent) between-subjects design. The percentage of beer consumed during the taste test was the primary outcome measure.ResultsAmong this largely undergraduate student population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…The study extends recent findings by Vasiljevic, Couturier, et al (2018) , by showing that the appeal of labels denoting alcohol strength decreases with decreasing communicated strength, regardless of whether strength is communicated verbally and/or numerically (%ABV). The results are compatible with the possibility that lower strength alcohol labeling could be used akin to alcohol unit labeling, with consumers using the labels to choose stronger products ( Jones & Gregory, 2009 ; Maynard et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study extends recent findings by Vasiljevic, Couturier, et al (2018) , by showing that the appeal of labels denoting alcohol strength decreases with decreasing communicated strength, regardless of whether strength is communicated verbally and/or numerically (%ABV). The results are compatible with the possibility that lower strength alcohol labeling could be used akin to alcohol unit labeling, with consumers using the labels to choose stronger products ( Jones & Gregory, 2009 ; Maynard et al, 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…Evaluations of other types of alcohol labeling may provide useful indications as to how the public might respond to lower strength alcohol labeling. For example, studies to date have shown that labeling the units of alcohol contained in a drink may carry unintended consequences, with the label being used as a reference cue to purchase stronger alcohol products ( Jones & Gregory, 2009 ; Maynard et al, 2018 ). Furthermore, in the absence of verbal descriptors of alcohol strength drinkers tend to underestimate the alcohol units contained in their drinks, reflected in the pouring of larger servings ( de Visser & Birch, 2012 ; Furtwängler & de Visser, 2016 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies suggest consumers would support the inclusion of more health information on labels and this might and prompt discussion amongst family and friends, as well as raise awareness (Miller, Ramsey, Baratiny, & Olver, 2016a). Another recent study suggested people do want to know about health risks as well as information on standard drink sizes and guidelines, but they may need more information than can be displayed on labels (Vallance et al, 2018) to a drinking occasion, which may lead to increased harms (Maynard, Langfield, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Any new warning label should ideally be trialled in both the laboratory and in the field before being introduced into the population, to mitigate the risk of any behavioral backfiring (Stibe & Cugelman, 2016). For example, qualitative research suggests that some young drinkers use ABV% information to find cost-effective ways of maximizing their alcohol consumption (Jones & Gregory, 2009;Maynard et al, 2017). While we think that few gamblers will want to purposively maximize their gambling losses, there are other issues from other public health domains of potential relevance gambling risk communication.…”
Section: Discussionmentioning
confidence: 99%